Fetal outcome in Premature Rupture of Membrane – A study conducted in a tertiary level hospital in Bangladesh (Mediscope, 2020)
Background: Perinatal mortality is high if premature rupture of membrane (PROM) occurs when fetuses are of previable gestational age.Objective: To find out the effect of premature rupture of membrane in pregnancy on its fetal outcome.Methods: A cross-sectional study was conducted in Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from February to July of 2008, on 50 pregnant women with more than 28 weeks of pregnancy both primigravid and multigravid with rupture of membranes prior to labour. Women who were admitted with rupture of membranes with established labour, or having antepartum hemorrhage, pre-eclampsia or eclampsia were excluded from the study. Out of 775, only 95 patients were admitted with history of premature rupture of membrane (PROM). Among those patients, 50 cases were included in this study as per inclusion and exclusion criteria. Then their mode of delivery and outcome of fetal parameters were recorded.Results: 48 live births were observed and there were 2 fetal losses. Among 48 live newborns, 28 (58.33%) were male and 20 (41.66%) were female. 54.16% of babies had APGAR score at 5 minutes after birth was >7 and those needed no treatment. APGAR score was 7 in 45.82% babies; all of them were treated and cured. Among the newborns, 52.08% babies had birth weight >2500 gm, 45.83% had their birth weight in between 1500 and 2500 gm, while 1 (2.08%) was between 1000 and 1500 gm. However, 22 (45.83%) were affected by the consequences of PROM and birth process. Among them, 36.36% developed jaundice, 29.27% suffered from birth asphyxia, and RTI and neonatal sepsis were evident in 18.18% each. 15% babies were treated conservatively in Department of Obstetrics, while 7% babies were treated in the Neonatal Ward under Department of Paediatrics after admission.There was no neonatal loss.Conclusion: Despite progress in obstetric and neonatal care over the past few years, fetal outcomes in pregnancies with PROM remains disappointing to date.Mediscope Vol. 7, No. 2: July 2020, Page 108-112